The pattern of screen-based media usage and it’s impact among school going children in Southern Rajasthan - Kalasua, Deepika; Chandel, Rajendra; Dindor, Rita; Topia, Jitin (International Journal of Contemporary Pediatrics, 2025)
Background: Screen-based media (SBM) has become an integral part of children’s lives, particularly in school-aged populations. Excessive screen time (ST) is associated with negative health outcomes, including physical, psychological, and academic effects. Understanding SBM use among school-going children is crucial for promoting healthy screen habits. Aim was to study the pattern of SBM use among school-going children and its impact on their health and academics. Methods: This cross-sectional study was conducted among school-going children from 1st to 12th grade in southern Rajasthan. A total of 3505 students from three private schools and one government school participated. Data were collected using a semi-structured, validated questionnaire addressing ST, media use, and its effects on health and academics. Descriptive statistics and chi-square tests were employed for analysis, with a significance level of 5%. Results: The majority of participants (64.99%) were aged 10-15 years, with a balanced gender distribution. Most children (57.54%) primarily used television, followed by WhatsApp (20.17%) and YouTube (17.83%). Screen-time of less than 1 hour was reported by 46.25% of children, while 13.60% exceeded 2 hours. Children with ST over 2 hours reported higher rates of irritability (33.3%), headaches (27.46%), and academic distractions. Parental screen habits influenced children’s ST, with 67.92% of children exceeding 2 hours having fathers with similar screen use. Conclusions: The study highlights that excessive ST is linked to adverse emotional, physical, and academic outcomes in children. Parents play a crucial role in moderating ST and guidelines tailored to age-appropriate screen-time are essential.